Identification of dynamic capabilities in open innovation - Edson Rodrigues de Aro; Gilberto Perez (Innovation & Management Review, 2021)
Purpose - This study aims to understand the interaction between capabilities inherent in open innovation and dynamic capabilities (sensing, seizing and transforming) as a source of competitive advantage. Design/methodology/approach - Qualitative method and grounded theory were used as guidelines for data collection and analysis. Findings - The study identifies a set of capabilities in the practice of open innovation related to dynamic capabilities, which indicates the importance of developing dynamic capability in the strategic management of internal and external knowledge in the company. Research limitations/implications - The number of interviewees approached herein do not allow generalizations, but the use of grounded theory through various strategies of data collection in the interviews allowed the triangulation of the data, increasing the credibility, validity and quality of the research. Originality/value This study presents capabilities identified in open innovation and their relationship with dynamic capabilities, identifying the importance of the dynamic capability in the strategic management of internal and external knowledge in the company as a source of competitive advantage.
Keywords: 650; Dynamic capabilities; Grounded theory; Open innovation